Strongly correlated superconductivity in a copper-based metal-organic framework with a perfect kagome lattice - Takenaka, T. (Sci Adv, 2021)
Metal-organic frameworks (MOFs), which are self-assemblies of metal ions and organic ligands, provide a tunable platform to search a new state of matter. A two-dimensional (2D) perfect kagome lattice, whose geometrical frustration is a key to realizing quantum spin liquids, has been formed in the π − d conjugated 2D MOF [Cu(3)(C(6)S(6))](n) (Cu-BHT). The recent discovery of its superconductivity with a critical temperature T(c) of 0.25 kelvin raises fundamental questions about the nature of electron pairing. Here, we show that Cu-BHT is a strongly correlated unconventional superconductor with extremely low superfluid density. A nonexponential temperature dependence of superfluid density is observed, indicating the possible presence of superconducting gap nodes. The magnitude of superfluid density is much smaller than those in conventional superconductors and follows the Uemura’s relation of strongly correlated superconductors. These results imply that the unconventional superconductivity in Cu-BHT originates from electron correlations related to spin fluctuations of kagome lattice.